(untitled) - McConnell, Campbell R. (Boston, MA., 2002)
sample of the book's new discussions and analyzes include: the switch to GDP accounting; Soviet economy in transition; economics and the environment; the crisis in American financial institutions; economics of information; strategic behaviour; public choice and tax analysis ...
Keywords: Kinh tế học,Economics